Kesiapan Digital Masyarakat Kampung Adat Naga pada Pelaksanaan One Village One Product - Nindi Aristi; Preciosa Alnashava Janitra (FISIP Universitas Atma Jaya Yogyakarta, 2019)
The implementation of One Village One Product (OVOP) program in Indonesia refersto the economic development of one village with one main product from the villagers’ creativity. Naga traditional village is one of traditional villages producing handicraft from natural resources. The use of ICT for promoting and marketing faces obstacles related to ICT adoption and digital readiness of the villagers. Case study method was deployed through in-depth interviews to five key informants. Based on the diffusion of innovation theory, the result shows the ICT adoption is in early majority level and their digital readiness is in the unprepared group